Public imunization sistem versus private immunization sistem: comparisons and attribution of nursing (Research, Society and Development, 2020)
The objective was to compare the immunization process of the public system with that of the private system, as well as to detail the attributions of the nurse in both immunization processes. Methodology: Retrospective comparative research, carried out through the analysis of the vaccination scheme of the public system and the private system, highlighting the nursing team attributions in both systems. Results: The organization of the information collected allowed the formation of a comparative framework between the public and private immunization systems, as well as the design of two categories, which are: 1) Nurses' responsibilities in the public health system; 2) Nurses’ assignments in the private healthcare system. Conclusion: The public health system has a broader coverage and more systematic and active research than the private health system. The private immunization system offers higher-quality care, with immunobiological agents not available in the SUS. In relation to the nursing team assignments, the public immunization network enables the nurse to proactively act and interact with the local and regional community. Meanwhile, the attributions of the nursing team in the private system are restricted to the actions more punctual and limited to users who seek the service at that time.